In Silico Study, Synthesis and Evaluation of New Indole-Hydrazones as Potential Antibacterial Agents - Yaseen S. Hamdoon; Mohammed K. Hadi (Iraqi Journal of Pharmaceutical Sciences, 2026)
Because pathogenic bacteria have gained resistance, bacterial illnesses are difficult to treat. Every year, a huge number of studies aimed at creating novel antibacterials are released. Shiff bases are an important field in organic synthesis due to their biological activities. Schiff bases also possessing an important range of pharmacological activities. Hybridization-combing two pharmacophores [heterocycle from starting molecule and synthesized hydrazones]  to form one molecule-is the important method in designing new drugs. The new compounds [hydrazones] derivatives were created using a multi-step process including synthesis of  indomethacin hydrazide by coupling agent reaction (EDC.HCL,HOBt) and then reaction with defferent aldehydes to form hydrazones , and thin-layer chromatography, ATR-FTIR, and 1HNMR spectroscopy were used to characterize them. Our objective is to create compounds with appropriate ADMET qualities that can be manufactured and employed in the future, as well as antibacterial activity based on molecular docking.Utilizing the fast resazurin micro titer assay MIC (minimum inhibitory concentration) method, the novel compounds' antibacterial properties were assessed. some compounds (IIIC) showed comparable activities to ciprofloxacin against S. aureus and comparable activity of ( IIIC , IIID ) against K. pneumonia other (IIIB) showed more potent against K. pneumonia, and in general all new compounds show  good activities against  E. coli, k .pneumonia , S. pyogenes  and S. aureus.